Improving agility and speed in playing soccer in first grade students in sd negeri no. 11 sungai apit kecataman sungai apit kabupaten siak - Syafri Syafri (Jurnal Ilmiah Pendidikan Scholastic, 2018)
Speed ​​and agility are the basic models in playing football and for the player is a successful capital to score, and keep the goal in check. By the ability of speed will facilitate the player in order to bring the ball. The problems of this research are: (a) How to improve the achievement mastery of football basics for students in the implementation of methods of demonstration?(B) How is the influence of demonstration methods on student learning motivation? The purpose of this research are (a) to know the improvement of learning achievement of soccer basics to students after the implementation of demonstration method, (b) to know the motivation to learn football basics after the implementation of demonstration method. This research uses action research as much as two rounds. Each round consists of two stages: design, activity and observation. Reflection and revise. The population of this research is first grade students in SD Negeri no. 11 Sungai Apit Kecamatan Sungai Apit Kabupaten Siak. From the data obtained as the result of the practice tests, observation sheet in teaching and learning process activities. From the analysis result, it can be seen that the students' learning achievement has increased from cycle I to II, cycle I (61.54%), cycle II (89,74%) for psychomotor domain, cycle I (84,62%).Cycle II (100%) for the affective domain Conclusions from this research is the demonstration of the method can be a positive influence on students' motivation to Class I Kelas I SD Negeri No.11 Sungai Apit Kecamatan Sungai Apit Kabupaten Siak and learning models can be used as an alternative physical education.